Strengthening Community Resilience During the Covid 19 Pandemic in Developing Tourism Based on Local Wisdom in Ubud Village - I Nyoman Putu Budiartha; I Nyoman Gede Sugiartha; A.A. Sagung Laksmi Dewi (Community Service Journal of Law, 2022)
As a higher education institution, Warmadewa University must ensure that it always obeys the Tridharma of Higher Education in accordance with the predetermined vision and mission. Now every lecturer is encouraged to be able to package community service activities both in groups and individually which will later show concern for the community. Community service activities can be carried out by providing enlightenment by providing legal counseling and consultation to the community in various fields of life in the field of environment and tourism. One thing that deserves attention is environmental conservation in Ubud Village where it is hoped that every Banjar Customary Community is required to have a plan for improving environmental management. Environmental conservation which is the values ​​of Balinese society, of course, in its application cannot be ignored even on the pretext of business interests. For the sake of maintaining community resilience from the influence of drugs from tourists who come to visit the tourist village of Ubud. Efforts that should be pursued and do not hesitate to carry out daily orders against tourists who come to Ubud, this impression is certainly expected for tourists who visit not to be free to carry narcotics which are prohibited by the government. of course the final result can strengthen the resilience of the community in Ubud Village against the influence of Narcotics which can damage the physical and mental resilience of the community.